Inbound tourism to Soviet Belarus during the Khrushchev’s thaw as a Cold War frontline - Huzhalouski, Alexander A. (Journal of the Belarusian State University. International Relations, 2023)
The author of this article examines the use of inbound tourism to the BSSR during the Cold War for promoting the Soviet way of life abroad. Despite a tripling of foreign visitors number during the Khrushchev’s thaw era, inbound tourism continued to serve the same primary purpose as in earlier decades: to convince foreign audiences of the indisputable merits of the socialist system and the Soviet way of life while enticing more people to visit. With this objective in mind, the technical framework and intellectual foundation for the reception of foreign tourists were built. At the centre of this endeavour was the agency “Intourist”, which worked closely with the Soviet government, Communist party organisations, and secret services. International guests were also received by the international youth tourism bureau “Sputnik” and the Belarusian society for cultural relations with foreign countries, which later changed its name to the Belarusian society for friendship and cultural relations with foreign countries. The impressions and attitudes of foreign visitors towards the Belarusian Soviet reality are reconstructed from a body of hitherto unstudied archive papers and magazines. Tourism was a crucial tool for the Soviet Union in projecting its ideology. It was becoming an increasingly significant weapon in its political confrontation with the West given the continually increasing number of tourists. Yet tourism was not only solidifying the opposing ideologies’ stances, it was also bringing them closer together, and public diplomacy was crucial in this process.